2001
DOI: 10.1016/s0022-5347(05)65529-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrarectal Lidocaine During Transrectal Prostate Biopsy: Results of a Prospective Double-Blind Randomized Trial

Abstract: Intrarectal lidocaine gel provides no significant therapeutic or analgesic benefit compared with lubricant alone for transrectal ultrasound guided biopsy of the prostate. In younger patients more discomfort is associated with this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 12 publications
6
55
0
Order By: Relevance
“…Cross-sectional studies on morbidity of prostate biopsies by Djavan et al 60 and Rodriguez et al 59 have concurred that younger patients had a higher discomfort rate. Studies included within this meta-analysis 27,37,38 confirm this. Despite the report by Naughton et al 61 that a 12-core biopsy procedure has no significant difference in pain compared to a 6-core procedure, others have shown that the pain level does increase significantly with increasing number of biopsies.…”
Section: Intrarectal Lignocainesupporting
confidence: 65%
See 1 more Smart Citation
“…Cross-sectional studies on morbidity of prostate biopsies by Djavan et al 60 and Rodriguez et al 59 have concurred that younger patients had a higher discomfort rate. Studies included within this meta-analysis 27,37,38 confirm this. Despite the report by Naughton et al 61 that a 12-core biopsy procedure has no significant difference in pain compared to a 6-core procedure, others have shown that the pain level does increase significantly with increasing number of biopsies.…”
Section: Intrarectal Lignocainesupporting
confidence: 65%
“…[34][35][36]42,44,[51][52][53]19,56 They were not specified in the remaining 15 trials. 14,[37][38][39][40][41]43,[45][46][47][48][49][50]54,55 For the trials assessing the efficacy of PPNBs, two types of controls were used. Either no anesthesia at all was given or an equivalent volume of normal saline injection was administered.…”
Section: Study Description and Validitymentioning
confidence: 99%
“…In this study, patients who underwent the use of an intrarectal gel with 2% lidocaine were compared with a control group (9,10). Pain scores were higher in the control group; however, there were no statistically significant differences between the groups when all pain scores were compared.…”
Section: Discussionmentioning
confidence: 93%
“…12,13 One recent study comparing rectal lidocaine gel to placebo (lubricant gel) found no benefit in pain control with the lidocaine. 16 Thus, it is not surprising that IVCS was far superior to rectal lidocaine gel in terms of pain and patient satisfaction, despite a far greater number of cores being obtained. During IVCS both narcotic (fentanyl) and amnestic (midazolam) agents are used.…”
Section: Discussionmentioning
confidence: 99%